Banking reform in Southeast Asia : the region's decisive decade - Cook, Malcolm (London ; New York: Routledge, 2008)
This book empirically examines banking reform in the economies of Southeast Asia as they sought to adapt to major developments in the global economic system over the past three decades, including the globalization of finance, the debt crisis of the 1980s and the 1997- 1998 Asian financial crisis.
Includes bibliographical references (p. [147]-153) and index.
rpm 16/05/13, ijb 07/03/2019
Loans
Keywords: Banks and banking; Monetary policy; Economic policy; Banking reform; Southeast Asia